Evaluating the impact of needs assessment models on autistic children’s participation in the habilitation process: protocol for a prospective observational study - Lundqvist, Lars-Olov; Sjödin, Linda; Karvonen, Evelina; Arnell, Susann (BMJ open, 2024)
IntroductionThe rising prevalence of autism spectrum disorder (ASD) among children poses significant challenges for healthcare services. Research has underscored the crucial role of children’s involvement in their healthcare. However, due to the intricate nature of ASD, marked by communication and social interaction differences, healthcare providers face challenges in tailoring their services to accommodate these children. This project aims to explore the impact of two distinct needs assessment models on children’s participation in the needs assessment process.Methods and analysisWe will conduct a prospective observational study comparing responses from children subjected to two different needs assessment procedures: survey-based and meeting-based. Supplementary data will be collected from the children’s parents/guardians and healthcare professionals. Data collection methods will include questionnaires, interviews and document analysis of individual habilitation plans. We aim to recruit 120 children aged 7–17 diagnosed with ASD but without intellectual disability, with 60 undergoing the survey-based needs assessment and 60 undergoing the meeting-based assessment. The primary outcome measure will be the perception of participation in the needs assessment procedure. Secondary outcomes will include the children’s quality of life and mental health; the parents’ knowledge of their child’s strengths, abilities and special needs; and the parents’ perception of the quality of collaboration with the healthcare team.Ethics and disseminationThe study received ethics approval from the Swedish Ethical Review Authority on 4 March 2024 (reference number 2024-00227-01). All children and their caregivers will receive both verbal and written information about the study before being asked to provide written informed consent to participate. The findings will be disseminated through publication in peer-reviewed journals and presentation at conferences. Additionally, a popular science report summarising the data and its interpretation will be published.Trial registration number NCT06381856.